Hopper discharge of elongated particles of varying aspect ratio: Experiments and DEM simulations. (November 2019) - Tangri, Henna; Guo, Yu; Curtis, Jennifer S.
Graphical abstract: Schematic of cylindrical particle discharge from a quasi-3D rectangular hopper. Highlights: Aspect ratio and coefficient of friction strongly affects discharge rate. DEM simulations can predict the flow behavior of elongated cylindrical particles. Hopper Cone Angle simulations show good match with Brown & Richards correlation. 'd' in Beverloo correlation is defined as longest dimension of cylindrical particles. Shape factor 'k' in Beverloo correlation is modified for cylindrical particles. Abstract: Steady flow of particulate or granular materials and bulk solids through a hopper plays a critical role in many industrial and process engineering applications. The present work investigates hopper discharge of non-spherical particles, specifically cylindrical particles, from a rectangular hopper. The behavior of steel cylindrical particles with varying aspect ratio (both varying diameter with constant length and varying length with constant diameter) was explored experimentally and via DEM simulations. In addition, the effects of fill height, particle friction, hopper orifice width and hopper cone angle on hopper discharge rate of non-spherical particles were studied via DEM simulations and compared with previously published experimental correlations, experimental results of spherical particles. The results indicate that DEM simulations are fully capable of reproducing trends that are established experimentally. The results with particles of high aspect ratio indicate a different trend than that previously observed with rounded particles. As the fill height increases, the mass discharge rate increases and then asymptotes; further increases in fill height cause a decrease in the mass discharge rate. Further, the effect of particle friction showed a significant influence on the hopper discharge behavior. In addition, a decrease in the hopper angle from 90 degree to critical angle 55 degree decreases the mass discharge rate flow and further decrease in hopper angle increases the discharge rate rapidly.